2021
DOI: 10.1525/elementa.2021.00027
|View full text |Cite
|
Sign up to set email alerts
|

First retrievals of peroxyacetyl nitrate (PAN) from ground-based FTIR solar spectra recorded at remote sites, comparison with model and satellite data

Abstract: Peroxyacetyl nitrate (PAN) is the main tropospheric reservoir of NOx (NO + NO2). Its lifetime can reach several months in the upper cold troposphere. This enables the long-range transport of NOx radicals, under the form of PAN, far from the regions of emission. The subsequent release of NOx through the PAN thermal decomposition leads to the efficient formation of tropospheric ozone (O3), with important consequences for tropospheric oxidative capacity and air quality. The chemical properties of PAN have stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…This is particularly true when a broad window is used, as is also the case for peroxyacetyl nitrate (PAN). 41 The first adjustment was to harmonise the two instruments (homemade and Bruker) time series by multiplying the Bruker time series by a factor of 0.9692 between 12/02/1999 and 09/10/2001. Afterwards, we multiplied the homemade instrument whole time series by a factor of 0.9467.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly true when a broad window is used, as is also the case for peroxyacetyl nitrate (PAN). 41 The first adjustment was to harmonise the two instruments (homemade and Bruker) time series by multiplying the Bruker time series by a factor of 0.9692 between 12/02/1999 and 09/10/2001. Afterwards, we multiplied the homemade instrument whole time series by a factor of 0.9467.…”
Section: Resultsmentioning
confidence: 99%
“…For the retrievals of CO, CH 3 OH, and HCOOH spectroscopic parameters are from the HITRAN 2008 line list database (Rothman et al, 2009). For the retrieval of PAN, H 2 O lines from HITRAN 2016 (Gordon et al, 2017) were used based on the recommendations of Mahieu et al (2021), while the spectroscopic parameters of all other species were sourced from HITRAN 2008. For the retrieval of C 2 H 4 , the updated ATM20 line list was used (Toon, 2022).…”
Section: Ftir Retrieval Methodsmentioning
confidence: 99%
“…Further details of the CrIS PANs retrieval can be found in Payne et al (2022). TES PAN could be biased high relative to CrIS PANs (Mahieu et al, 2021). In retrievals based on groundbased FTIR measurements covering the spectral regions used by both instruments, Mahieu et al (2021) showed that PAN values retrieved using the retrievals using the 790 cm −1 spectral feature utilized by CrIS were biased low relative to those using the 1150 cm −1 spectral feature used for the TES PAN retrievals.…”
Section: Cris Observationsmentioning
confidence: 99%